THE FINNISH EDUCATION AND QUALIFICATIONS SYSTEMS - Petri Lempinen (Образование и наука)
The paper describes the Finnish perspective on introducing the national qualifications framework based on learning outcomes and competences. The issue is analyzed in a broader context of successful history of Finnish education and realization of lifelong training strategy. The authordemonstrates the education policy development in Finland and the role of different parties in its implementation, as well as a conflict of interests and obstacles that slow down the adoption of the national qualifications framework.